Closed-form design of Wilkinson power divider with broadband harmonic suppression and size reduction - Yang, N. (2013)
This paper presents a novel design concept of power divider, capable of broadband harmonic suppression and realized by replacing the branch lines of the modified Wilkinson power divider with wideband open-stub bandstop filters. For verification, a power divider operating at 1 GHz is designed, fabricated and tested. The realized power divider occupies a core size of only 26.3 mm × 18.1 mm, or 0.15λg × 0.10λg. Measurements show that broadband harmonic suppression is achieved from 1.95 GHz to 6.00 GHz with spurious attenuation better than 30 dB.